Study on characteristics of particulate emission of diesel aftertreatment with reciprocating flow. Issue 4 (22nd February 2021) - Deng, Yangbo; Wang, Xiaolong; Li, Rongrui; Han, Zhitao; Wu, Hongwei; Dong, Jingming; Cui, Wenbin; Guo, Yang
Abstract: In this article, in order to optimize diesel aftertreatment system with periodically reciprocating flow (PRF), an experimental study is conducted to investigate its characteristics such as pollution emissions, regeneration of diesel particulate filter (DPF), concentration, and size distribution of particulate matter (PM) escaped as well as temperature distribution under unidirectional flow and PRF operating conditions. The effects of reciprocating flow cycle and exhaust gas flow on the performance of aftertreatment system are investigated in detail. The energy efficiency analysis of the aftertreatment system is also carried out. Experimental results show that (a) as the temperature is lower than the light‐off threshold of combustible gas, the aftertreatment system cannot restrain the formation of second particles under the low‐temperature condition of unidirectional flow; and (b) the aftertreatment system demonstrates excellent performance of trapping particles and filter regeneration as the symmetrical temperature distribution is formed. The PM filter efficiency α PM is 92%, and the specific energy consumption β is 124% for symmetrical temperature distribution; (c) the increase in reciprocating flow cycle could lead to the shifting of the temperature profiles, and this would affect the particle size distribution; (d) a certain increase in exhaust gas flow from engine would have insignificant change for the temperature distribution; and (e) the critical energy efficiency η c of the system could reach 96.61%. Abstract : A diesel aftertreatment system with periodically reciprocating flow can demonstrate excellent performance of trapping particles, and filter regeneration as a symmetrical temperature distribution is formed. The increase in reciprocating flow cycle can lead to the shifting of the temperature profiles, and this would affect the particle size distribution. Certain increases in qv do not alter perfect temperature distribution characteristic.